CONCEPTUAL SCOPE OF THE CONCEPT OF POLITICAL FAMILISM - Самброс, А.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article deals with conception of political familism in the context of modern political science. It gives a brief analysis of the history of studying political familism and identifies the main current problems of the theory in the modern world (the liaison between practices of political familism and the nature of political regimes). Much attention is paid to the relationship between the degree of interpersonal trust in society and practices of political familism.